[Antal Kiss 2]
1972-1976, holiday at the sea, hotels harbour, France, Paris, Monte Carlo, nice view from the bus through Switzerland & Germany, agricultural co-operative,watering on the fields, horse carriage, weekend house family together, 1975 Maria name-day, excursions in Hungary